QARAQALPAQ TILINDEGI «QOL» KOMPONENTLI SOMATIKALÍQ FRAZEOLOGIZMLER - Shınnazarova, S.J. (ILIM hám JÁMIYET, 2024)
The article examines phraseological units with the component “hand” in the Karakalpak language. Somatisms are proven using examples from works of art. Linguistic variants and semantics of somatic phraseological units with the component “hand” are analyzed.